Risk of lymphoid neoplasms in a Swedish population-based cohort of 337, 437 patients undergoing appendectomy. (3rd May 2016) - Mohammadi, Mohammad; Song, Huan; Cao, Yang; Glimelius, Ingrid; Ekbom, Anders; Ye, Weimin; Smedby, Karin E.
Abstract: Objective Appendectomy remains one of the most common surgical procedures, but possible long-term consequences for health and disease are incompletely investigated. The appendix forms part of the secondary lymphoid system and appendectomy has been associated with increased risks of hematolymphoproliferative malignancies in some studies.Materials and methods We examined the risk of lymphoid neoplasms in a large cohort of 337, 437 appendectomised patients <60 years of age in Sweden 1975–2009. We estimated relative risks of non-Hodgkin lymphoma (NHL) and major subtypes, Hodgkin lymphoma (HL), chronic lymphocytic leukaemia (CLL), myeloma, and acute lymphoblastic leukaemia (ALL) versus the general population using standardised incidence ratios (SIRs) with 95% confidence intervals (CIs).Results There was no increased risk of NHL (SIR = 0.97, 95%CI 0.88–1.06), major NHL subtypes, CLL (SIR = 0.87, 95%CI 0.70–1.06), myeloma (SIR = 1.14, 95%CI 0.96–1.33) or ALL (SIR = 1.10, 95%CI 0.80–1.47) following appendectomy. An increased risk of HL was observed among patients diagnosed with appendicitis (SIR = 1.29, 95%CI 1.07–1.54, p =0.007), especially individuals aged <20 years at surgery (SIR = 1.43, 95%CI 1.11–1.82), and for the nodular sclerosis subtype of HL (SIR = 1.55, 95%CI 1.01–2.27). A marginally increased risk of myeloma was noted among men, but the association was limited to the first few years of follow-up.Conclusion Appendectomy is not associated with any notable increase in risk of lymphoid neoplasms. A small increased risk of HL following appendicitis (rather than appendectomy per se ) could reflect a true association, or shared susceptibility to infection/inflammation among individuals prone to develop HL. The association observed for myeloma may be explained by chance or surveillance bias.